Using the Cardiac–Electrophysiological Balance Index to Predict Arrhythmia Risk After Colonoscopy - Seyit Ali Volkan Polatkan; Seyda Gunay-Polatkan; Ozgen Isik; Deniz Sigirli (Medicina)
Background and Objectives: Colorectal cancer is the second leading cause of cancer-related deaths in the U.S., and colonoscopy is a critical tool for colon cancer screening and diagnosis. Electrolyte disturbances and autonomic nervous system dysfunction that may occur due to bowel preparation and the colonoscopy procedure itself may play a role in the development of cardiac arrhythmia. This study aimed to assess the index of cardiac–electrophysiological balance (iCEB) to predict ventricular arrhythmia risk related to colonoscopy. Materials and Methods: Patients undergoing elective colonoscopy with a normal sinus rhythm were included. Electrocardiography (ECG) recordings both before bowel preparation and after the colonoscopy procedure were obtained. Values of the index of cardiac–electrophysiological balance (iCEB) were compared. Results: Among 36 patients, it was determined that the heart rate values of the patients before bowel preparation were higher than the heart rate values after colonoscopy [74.5 (60–108) bpm vs. 68.5 (53–108) bpm, p = 0.021]. The duration of QT interval increased (370.9 ± 27.8 ms vs. 398.7 ± 29.4 ms, p < 0.001) and the iCEB increased from 4.1 ± 0.5 to 4.5 ± 0.6 (p < 0.001), indicating a significant post-procedural risk of ventricular arrhythmias. Conclusions: These findings suggest that routine iCEB assessment post-colonoscopy could identify high-risk patients requiring closer monitoring.